2021
DOI: 10.1101/2021.01.23.21250164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of the knowledge, preferences and concern regarding the prospective COVID- 19 vaccine among adults residing in New Delhi, India-A cross sectional study

Abstract: BackgroundUnderstanding the perception and concerns of people about COVID-19 vaccine in developing and populous country like India will help in understanding demand for the vaccine and further tailoring out public health information and education activities before the launch of the vaccine. The study was carried out to assess the present state of knowledge people have about the probable vaccine for COVID-19, to know the preferences of respondents about this vaccine and to learn the expectations and apprehensio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
(18 reference statements)
0
19
2
Order By: Relevance
“…The study's results also found evidence that COVID-19 vaccine efficacy affected individuals' demand for the vaccine, including both the overall willingness to get vaccinated and the WTP for the vaccine. Several previous studies have found that COVID-19 vaccine attributes affect the demand for the vaccine [26,[42][43][44][45][46][47]. A substantial and significant effect of vaccine efficacy was found in Australia, where consumers were found to be willing to pay US$23.92 for a 1% increase in vaccine efficacy; this implies a US$360 increase in WTP when comparing, for example, COVID-19 vaccines with 84% and 99% efficacy levels (minimum and maximum levels used in that study).…”
Section: Discussionmentioning
confidence: 99%
“…The study's results also found evidence that COVID-19 vaccine efficacy affected individuals' demand for the vaccine, including both the overall willingness to get vaccinated and the WTP for the vaccine. Several previous studies have found that COVID-19 vaccine attributes affect the demand for the vaccine [26,[42][43][44][45][46][47]. A substantial and significant effect of vaccine efficacy was found in Australia, where consumers were found to be willing to pay US$23.92 for a 1% increase in vaccine efficacy; this implies a US$360 increase in WTP when comparing, for example, COVID-19 vaccines with 84% and 99% efficacy levels (minimum and maximum levels used in that study).…”
Section: Discussionmentioning
confidence: 99%
“…The acceptability ratio determined in this research is very low than the previous studies done in other countries such as in China, India, Saudi Arabia, and Bangladesh. The studies reported about willingness of 83.8% 14 , 79.5% 15 and 64.7% 16 in China, India and Saudi Arabia, respectively. The low level of acceptance of vaccine among participants of this study could be linked with the literacy rate, less access to reliable information and socioeconomic dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In first phase, providing vaccine to healthcare workers and front-line workers including police, sanitary workers, paramilitary forces [25] . Though initially there was vaccine hesitancy particularly in rural and tribal parts of India, but constant government and public awareness campaigns has reduced the hesitancy and studies published from Delhi showed vaccination acceptance of 79.5% and another study published from West Bengal showed vaccination acceptance of 77.27% [26,27] . India registered new world record of administering more than 1 crore doses of vaccine in a single day on 27 th august 2021 [28] .…”
Section: Vaccinationmentioning
confidence: 99%